2017
DOI: 10.1007/s00540-016-2300-4
|View full text |Cite
|
Sign up to set email alerts
|

Swallowing action immediately before intravenous fentanyl at induction of anesthesia prevents fentanyl-induced coughing: a randomized controlled study

Abstract: The swallowing action immediately before intravenous fentanyl may be a simple and clinically feasible method for preventing FIC effectively. Clinical trial number: UMIN000012086 ( https://upload.umin.ac.jp/cgi-open-bin/ctr/ctr.cgi?function=brows&action=brows&type=summary&recptno=Rn000014126&language=J ).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“… Goyal et al (2017) found that preoperative incentive spirometry before giving fentanyl would suppress FIC, along with the secondary benefit of preventing postoperative pulmonary complications. Furthermore, Sako et al (2017) showed that swallowing action immediately before intravenous fentanyl also reduce the incidence of FIC from 40.4% to 14.0%.…”
Section: Prevention and Treatment Of Fentanyl-induced Coughmentioning
confidence: 97%
“… Goyal et al (2017) found that preoperative incentive spirometry before giving fentanyl would suppress FIC, along with the secondary benefit of preventing postoperative pulmonary complications. Furthermore, Sako et al (2017) showed that swallowing action immediately before intravenous fentanyl also reduce the incidence of FIC from 40.4% to 14.0%.…”
Section: Prevention and Treatment Of Fentanyl-induced Coughmentioning
confidence: 97%
“…We read with interest the recent article by Sako et al [1] that described a swallowing maneuver that reduces the incidence of fentanyl-induced coughing (FIC) (from 40.4 to 14.0%) when performed more than five times immediately before intravenous fentanyl administration [1]. Undoubtedly, Sako et al [1] have proposed a simple yet effective method to suppress FIC.…”
Section: Abstract Opioid · Cough · Fentanyl · Swallowingmentioning
confidence: 99%
“…Undoubtedly, Sako et al [1] have proposed a simple yet effective method to suppress FIC. Although they provided a possible explanation for their finding, the mechanism underlying FIC suppression by the swallowing maneuver was not well clarified.…”
Section: Abstract Opioid · Cough · Fentanyl · Swallowingmentioning
confidence: 99%
“…We thank Dr. Ho et al [1] for the comments regarding our recent manuscript [2]. Although µ-opioid generally possesses antitussive potential, fentanyl often induces cough (fentanyl-induced cough, FIC) during the induction of anesthesia.…”
Section: To the Editormentioning
confidence: 99%
“…However, the mechanism is still unclear. We speculated [2] that the afferent vagal nerve fiber was activated by swallowing, which might disturb FIC. Jun et al [3] reported that during swallowing laryngeal adductor muscle activity increases to close the glottis and upper esophageal sphincter activity leads to prevent aspiration.…”
Section: To the Editormentioning
confidence: 99%